Pragmatisches Denotat der Ausrufeformen im Vergleich: Deutsch-Arabisch Eine kontrastive Untersuchung - Abbas, Asma Mohammed (Al-Adab Journal, 2020)
This paper studies the pragmatic meanings of exclamation in both the German and Arabic languages. It is considered an attempt to know all the different pragmatic aspects of the sentence that carries the exclamatory meaning in both languages. It also addresses the multiple grammatical forms of exclamation in both languages. The research seeks to identify similar grammatical structures of the exclamatory sentences ​​in an attempt to reach a clear possibility to translate the style of the different types of sentences under study by analyzing their pragmatic meaning in order to overcome the difficulties that face the translator and the possibility of separating them from the rest of the types of sentences as they overlap with the different types of sentences.